Integration of the Noble Essence of Pancasila with the Perspective of the Islamic Religion - Alif Lukmanul Hakim (Universitas Muhammadiyah Enrekang, 2023)
This article is about Pancasila values related to the teachings of Islam. Pancasila has values that provide guidelines for the life of the nation and state in Indonesia. Of course values are born correlated with the teachings of Islam. Pancasila is the philosophy of life for the nation and state which is a fundamental value for the Indonesian people. This research was conducted using literacy and document research methods. Several scientific journals, previous research, and related literature sources collected data relating to the integration of Pancasila values with the Islamic religion which were then analyzed and concluded in written form. Islamic Shari'a plays a role in creating every essence of the precepts in Pancasila. Before independence, the BPUPKI committee held a meeting to make Pancasila a meaningful blend of opinions, ideology and the background of the Indonesian people. This article will discuss more deeply about Islamic law and Pancasila and their relationship. This article produces and discusses the integration and synergy between the essence contained in the Pancasila precepts and the perspective of the Islamic religion.